Assessment and Management of Strength and Durability of Composite Glass Elements - Yurii Rodichev (Challenging Glass Conference, 2016)
The composite load bearing glass elements have the many advantages as compared with the massive glass structures [1, 2]. The use of high strength, plasticity or viscous behavior of the additional structural elements increases the safety and strength of glass composite. However, the main peculiarities of glass composite mechanical deforming, strength and fracture are remain induced by the primary influence of elastic and brittle nature of glass components on the whole composite structural behavior [1]. The technical approach for the assessment and management of the strength and durability of composite glass elements was developed basing on this position. The management of glass composite strength foresees the use some control tests of the mechanical state of glass components in the composite together with the specific constructional and technological solutions for strength increasing and maintenance in different service conditions [1-5]. Some results of the assessment and management of quality, strength and life time of the annealed and strengthened glass elements as the components of composites with increased carrying capacity are discussed in a paper.